Efficacy of Concanavalin-A conjugated nanotransfersomal gel of apigenin for enhanced targeted delivery of UV induced skin malignant melanoma - Manmohan S. Jangdey; Chanchal Deep Kaur; Swarnlata Saraf (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
The aim of present study was to develop the efficient targeting of Concanavalin-A conjugated nanotransfersomal gel to bind directly to melanocytes gel layer against UVB induced skin carcinoma. Carbopol loaded nanotransfersomal gel have prepared by modified rotary evaporation sonication technique & conjugated synthesized by carbodiimide method and they were characterized the morphology, zeta potential, penetration and cell viability. In vitro release studies & skin permeation have determined using Franz diffusion cell and confocal laser scanning microscope (CLSM). The conjugated formulation showed vesicles size, polydispersity index, zeta potential and % conjugation efficiency of 179.0 ± 0.32 nm, 0.197 ± 0.07, 35.1 ± 0.21 mV and 89.73 ± 1.29% respectively. The surface morphology was confirmed by transmission electron microscopy (TEM) and FTIR to make sure the compatibility among its ingredients. Con-A conjugated nanotransfersomal gel showed toxicity on melanoma (A375) in a concentration range of 0.4–2.0 mg/mL, but less toxicity toward HaCaT cells. The MTT assay has analyzed against two different cell lines, to determine their anti-cancer potentials and their targeting ability. Conjugated formulation were found to decrease the cell viability, higher skin targeting efficacy in in-vitro & in-vivo. Concanavalin conjugated nanotransfersomal gel of apigenin promise an efficient and economic approach for the skin cancer.